The effect of intravenous infusion of N-acetyl cysteine in cirrhotic patients undergoing liver resection: A randomized controlled trial - Eman Sayed; Khaled Gaballah; Eman Younis; Khaled Yassen; Abo K El-Einen (Wolters Kluwer Medknow Publications, 2017)
Background and Aims: Liver resection can lead to hepatocellular dysfunction. The aim was to evaluate the effect of N-acetyl cysteine (NAC) on liver enzymes (alanine aminotransferase [ALT] and aspartate aminotransferase [AST]), international normalized ratio (INR), C-reactive protein (CRP), and intercellular adhesion molecule 1 (ICAM 1) in cirrhotic patients undergoing liver resection. Material and Methods: A randomized controlled trial (RCT), Pan African Clinical Trial registry (PACTR201508001251260). 60 Child A patients were studied. NAC group (n = 30) received intravenous infusion of NAC 10 g/24 h in 250 ml of 5% dextrose during surgery and for 2 days. Controls (C) (n = 30) received a similar volume of 5% dextrose. All above parameter were measured during and after surgery. Results: ALT and AST were significantly elevated after surgery, but to a less extent with NAC versus C (day 3; 118.3 ± 18.6 vs. 145.4 ± 14.0 U/L. P < 0.01) and (121.5 ± 19.5 vs. 146.6 ± 15.1 U/L, P = 0.00), respectively. Lower serum CRP and ICAM 1 with NAC versus C on day 3 (44.2 ± 13.4 vs. 68.7 ± 48.2 mg/l, P = 0.003), (308.8 ± 38.2 vs. 352.8 ± 59.4 ng/ml, P = 0.002), respectively. Hospital stay was shorter with NAC versus C (6.1 ± 0.8 vs. 6.9 ± 1.2 days, P = 0.006). Duration of surgery, INR, and hemodynamics were comparable. Conclusion: Prophylactic NAC in hepatic patients undergoing liver surgery attenuated postoperative increase in transaminases, ICAM 1, and CRP blood levels. The impact of these findings and the cost benefit of reduced hospital stay on enhanced recovery after surgery needs to be evaluated.